Distinct Influences of Mothers and Fathers on Kindergartners' Numeracy Performance: The Role of Math Anxiety, Home Numeracy Practices, and Numeracy Expectations. Issue 8 (17th November 2017) - del Río, M. Francisca; Susperreguy, Maria Ines; Strasser, Katherine; Salinas, Viviana
ABSTRACT: The current study analyzed maternal and paternal differential influences on numeracy performance in kindergarten children. Participants were 180 Chilean children from backgrounds of low and high socioeconomic status (SES), their mothers, and their fathers. A path analysis was used to explore the influences of both maternal and paternal numeracy practices on children's numeracy performance and the influences of maternal and paternal expectations and anxiety on those activities. Research Findings : Results showed that mothers and fathers who endorse higher numeracy expectations for their children and who report lower levels of math anxiety also report engaging more frequently in advanced numeracy practices with their children. Mothers'—but not fathers'—engagement in numeracy practices at home predicted children's numeracy performance. Also, low-SES mothers engaged more frequently in numeracy practices with their children, and mothers in general engaged more often in numeracy activities with girls than with boys. Practice or Policy : These findings improve understanding of how maternal and paternal processes relate differently to numeracy performance in kindergarten children. Moreover, these results highlight the need to take into account parents' numeracy attitudes and practices, as well as their SES, when designing interventions directed at increasing family support for math achievement.